PENILAIAN TINGKAT SERVICE TOKO ONLINE DAN ANALISIS PERBANDINGAN PERCEIVED PERFORMANCE - sasa ani arnomo (Computer Based Information System Journal, 2018)
The sale and purchase transaction process are carried out through the internet using internet media using both smartphones and computers. The development of the internet has undergone a product sale and purchase transaction process. Various buying and buying transactions can only be done face-to-face, now it can be done through the internet called online stores. To support the freedom of online stores, a website or smartphone application is an important component that presents information in the form of text, images, sounds and others that are presented to find information in tracing and exploring information virtually on certain media. Many online sales websites will be seen from different levels of service. Therefore, the purpose of this analysis is to assess the performance of online store websites. The research method used in this study is a quantitative descriptive research method with comparative analysis techniques. The results obtained from the level of online store service levels show that the percentage of satisfaction is 64.09% and an increase in performance perceptions occur because each online store has different features and different times.